Constitutive modelling of Mullin's effect in swollen nitrile butadiene rubber under cyclic loading / Irmalisa Samsuri - Irmalisa , Samsuri (2012)
Under cyclic loading, hyperelastic materials exhibit a particular stress softening behaviour called Mullin’s effect. Few efforts have been done to propose a mathematical model to represent this behaviour in rubber material. However, all attempts are only focusing on dry rubber. The study of Mullin’s effect in swollen rubber is quite important since a lot of parts or components made from rubber are exposed to aggressive solvent such as biodiesel. With the application of cyclic loading, the degradation of material becomes more rapid and leading to fatigue. In this study, the constitutive modelling of Mullin’s effect in swollen Nitrile Butadiene Rubber (NBR) is addressed. For this purpose, the viewpoint of Continuum Damage Mechanics by Chagnon et al. (2004) is considered and extended in order to take into account swelling level. The Fung strain energy density function is chosen to describe the mechanical behaviour of the hyperelastic rubber. The theoretical model developed is then plotted and the result is compared with the experimental. Results show a qualitative good agreement between the model and experiment. Although the model is able to capture the Mullin’s effect phenomenon, further study needed in order to determine this behaviour in compressible material.